Impact of a modified produce prescription program on fruit and vegetable intake in an HBCU - Janet Antwi; Redeemer Kofi Agbolegbe; Obed Akwaa Harrison; Kenneth Ofori-Panyin; Prince Dunyo; Mercedes Udodirim Guimaraes; Nora Bosio Onyeani (PLoS ONE, 2026)
Background Limited access to fruits and vegetables remains a significant barrier among underserved populations, particularly within Historically Black Colleges and Universities (HBCUs). Evidence from previous studies suggests that prescription programs, which provide incentives for fresh produce consumption, are effective in enhancing dietary quality and alleviating food insecurity. Objective This pilot investigation assessed the impact of a tailored produce prescription intervention on changes in fruit and vegetable consumption among students at a Historically Black College and University (HBCU). Methods Fifty-five students were assigned to an intervention (n = 28) or control group (n = 27); both received nutrition education and cooking demonstrations, while the intervention group additionally received biweekly personalized produce bags. Fruit and vegetable intake was assessed using a 10-item dietary screener, supported by 24-hour recalls and food frequency questionnaires. Changes in intake were evaluated using descriptive statistics, chi-square tests, and Wilcoxon signed-rank tests. Results Compared with the control group, the intervention group reported higher intake frequencies of cooked beans (χ 2 = 17.63, p = 0.014), while the intake of non-deep-fried vegetables approached statistical significance (χ 2 = 16.82, p = 0.052). Notably, only the intervention group experienced increases from baseline to endline in the intake of 100% fruit juice (Z = −2.199, p = 0.028), fruits (Z = −2.199, p = 0.028), green leafy vegetables (Z = −2.195, p = 0.028), cooked beans (Z = −2.776, p = 0.005), other non-deep-fried vegetables (Z = −2.292, p = 0.022), and tomato sauce (Z = −2.026, p = 0.043). Conclusion The results of a modified produce prescription program revealed favorable within-group changes in the frequency of consumption of several fruit- and vegetable-related foods. While most between-group differences at endline were not statistically significant, observed patterns suggest potential promise and support the need for larger, adequately powered studies to evaluate the impact more rigorously.